2015
DOI: 10.1371/journal.pone.0118335
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive Gating of Kv Channels

Abstract: K-selective voltage-gated channels (Kv) are multi-conformation bilayer-embedded proteins whose mechanosensitive (MS) Popen(V) implies that at least one conformational transition requires the restructuring of the channel-bilayer interface. Unlike Morris and colleagues, who attributed MS-Kv responses to a cooperative V-dependent closed-closed expansion↔compaction transition near the open state, Mackinnon and colleagues invoke expansion during a V-independent closed↔open transition. With increasing membrane tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Voltage-gated potassium and sodium channels are known to be sensitive to mechanical stimulation, as their activation by membrane depolarization is modulated by membrane stretch (Laitko et al, 2006;Beyder et al, 2010;Schmidt et al, 2012;Hao et al, 2013). However, whether the effect of membrane stretch is mediated by their four VSDs or their pore domain is a subject of debate (Tabarean and Morris, 2002;Schmidt et al, 2012;Morris et al, 2015). Because the Hv1 channel lacks the pore domain and has a dimeric, rather than tetrameric, structural organization, it represents a simpler model to study how mechanical forces affect VSDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voltage-gated potassium and sodium channels are known to be sensitive to mechanical stimulation, as their activation by membrane depolarization is modulated by membrane stretch (Laitko et al, 2006;Beyder et al, 2010;Schmidt et al, 2012;Hao et al, 2013). However, whether the effect of membrane stretch is mediated by their four VSDs or their pore domain is a subject of debate (Tabarean and Morris, 2002;Schmidt et al, 2012;Morris et al, 2015). Because the Hv1 channel lacks the pore domain and has a dimeric, rather than tetrameric, structural organization, it represents a simpler model to study how mechanical forces affect VSDs.…”
Section: Discussionmentioning
confidence: 99%
“…Hv1 mechanosensitivity thus provides a mechanistic link between channel activation in microglia and brain damage after stroke. Beyder et al, 2010;Schmidt et al, 2012;Morris et al, 2015), we investigated the response of Hv1 to this particular type of mechanical stimulus. We found that membrane stretch strongly affects Hv1 gating and that the channel's activation rate is the most mechanosensitive parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of stretch on ion channel populations has been principally investigated using localized membrane suction as a method for cell membrane deformation (Beyder et al, ; Morris & Juranka, ; Morris, Prikryl, & Joós, ; Wang et al, ). Although this allows simultaneous deformation and ion current recording, it does not closely replicate strains occurring in nerves in vivo, where the whole cell is subject to deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other sensory systems suggested the mechanoreceptors convert mechanical stimuli to receptor potentials via activation of ionic channels. The opening of the mechanosensitive channel is selective to sodium or potassium ions and the channel activation was voltage-dependent [ 17 , 27 , 28 ]. However, studies on the mechanosensitive channel of putative aortic baroreceptor neurons found that the channel currents appeared to be linear to the voltage and the channel opening frequency increased with pressure.…”
Section: Discussionmentioning
confidence: 99%